If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7z + -14 + -1z + 2 = 0 Reorder the terms: -14 + 2 + 7z + -1z = 0 Combine like terms: -14 + 2 = -12 -12 + 7z + -1z = 0 Combine like terms: 7z + -1z = 6z -12 + 6z = 0 Solving -12 + 6z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 6z = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 6z = 0 + 12 6z = 0 + 12 Combine like terms: 0 + 12 = 12 6z = 12 Divide each side by '6'. z = 2 Simplifying z = 2
| 4a^2-49=0 | | x(7x+1)(x-3)=0 | | -x+5=-16 | | (x^2+y^5)(x^2-y^5)=0 | | 5x-8x+5=0 | | 4.8y=11.04 | | 3x^2+30x-77=0 | | 0.10x+.05(14-x)=.10(15) | | -2x(3x+1)=-4(2x)-4 | | (x^2+5y^5)(x^2-y^5)=0 | | -x^2+2.5x+1=0 | | 8x-6=180 | | (2v+5)(2v-5)=0 | | 2(-2)-3(4)-4(-1)= | | X^2(8-X^2)=0 | | 2d-31=-9d+24 | | x+.6x=5 | | 176-4x=32x+20 | | (x)(x+2)=68 | | 13p^2=24 | | x+14=114 | | 13p^2=0 | | 5(x+3)=70 | | 5g-3=7 | | 0=150-5x-x^2+117 | | -4.1-5x-1.4-x=-5x-1.2 | | (x-4)8=16 | | 3f+5=17 | | x=22-3.5x | | 5x-5=8-7x | | 9x-(2x+7)=3x-43 | | 0=250-9x-x^2+112 |